Synthesis of monodispersed bimetallic palladium-copper nanoscale colloids - Bradley, John S; Hill, Ernestine W; Klein, Carl; Chaudret, Bruno; Duteil, Anne (Chemistry of materials, 1993)
Bimetallic clusters have been the subject of many studies of the surface chemistry and catalytic properties of metal crystallites on solid supports. Mixtures of palladium acetate and copper acetate were refluxed in 2-ethoxyethanol in the presence of poly(vinylpyrrolidone) to give 40-[angstrom] alloy nanoclusters. TEM and EDAX analysis showed that the particles were homogeneously bimetallic and crystalline, with a composition determined by the ratio of the metal acetates used. Carbon monoxide adsorbed on the colloidal particles binds reversibly to both metals. 9 refs., 3 figs.